Characteristics of Ovarian Tumor Clinicopathology: 3 Years Experience - Inge Mellangga Putri; Dewi, Citra; Ardesy Melizah Kurniati (Jurnal RSMH Palembang, 2023)
Ovarian tumors account for 30% of all malignancies in the female genital organs and can be benign, borderline, and malignant tumors. According to World Health Organization (WHO) based on the origin of tumor cells are divided into three groups, namely epithelial tumors, cord-stromal sex, and germ cells where the most types are epithelial types. This study aims to determine the clinicopathological characteristics of ovarian tumors carried out in a descriptive observational manner. Samples using secondary data of ovarian tumor patients who came to the Anatomical Pathology Section of Dr. Mohammad Hoesin Hospital Palembang for the 2018-2020 period who met the inclusion criteria using the total sampling technique obtained 325 secondary data all included as research samples. The results of the study found proportional morbidity rate of ovarian tumors based on the type of histopathology most epithelial tumors obtained by 55%. The highest ovarian tumor patients in the age group of 20-34 years are 91 people, the most common type of tumor histopathology is epithelial tumors as many as 179 cases where mucinous tumor most occur at the age of 20-34 years as many as 23 people, the most growth patterns are cystic 140 cases, the most ovarian tumor behavior is malignant tumors as many as 143 cases. Malignant ovarian tumors are most common in the age group of 20-34 and 45-54 years, which is 37 people each. The cystic growth pattern is most prevalent in benign ovarian tumors, which are as many as 87 cases. It can be concluded that the most common ovarian tumors are epithelial tumors. Based on age and growth patterns, most ovarian tumors occur at the age of 20-34 years with cystic growth patterns. The behavior of most ovarian tumors is malignant tumors.